Pengujian Infusa Rebusan Bunga Telang (Clitoria ternatea) Sebagai Pewarna Alami Sediaan Apus Darah Tepi (SADT) - Nur Aini Hidayah Khasanah; Fajar Husen (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2023)
Telang flower (Clitorea ternatea) is a flower that belongs to the endemic plants that are often found in Ternate. C. ternatea belongs to the Fabaceae family of leguminous plants and is the world's most prominent family of flowering plants. C. ternatea contains a lot of blue pigments or cyanos known as anthocyanins. These dyes have great potential as alternative dyes to replace methylene blue and are potential blood cell dyes. This study aimed to examine the potential of the anthocyanin content in the butterfly pea flower infusion as a natural differential dye for erythrocytes and leukocytes. This research method is descriptive in nature, in which the results of making cytological preparations in the form of capillary smears of human blood are stained with butterfly pea flower infusion at a concentration of 10%. The stained spots were then observed using a light microscope at 400x magnification. The colouring results of butterfly pea flowers were compared with a standard dye, Giemsa dye. The results showed that a 10% concentration of butterfly pea flowers stained erythrocytes but did not stain leukocytes well, while Giemsa's staining significantly stained well. The results also showed that butterfly pea flower infusion could only differentiate stained erythrocytes and unstained leukocytes but could not differentiate the types of leukocytes. Further research can be carried out by extracting anthocyanins from butterfly pea flowers and fractionating them to isolate single anthocyanin compounds that can potentially be dyed.